Obesity-Related Chronic Kidney Disease: Principal Mechanisms and New Approaches in Nutritional Management - Stasi, Alessandra; Cosola, Carmela; Caggiano, Gianvito; Cimmarusti, Maria Teresa; Palieri, Rita; Acquaviva, Paola Maria; Rana, Gloria; Gesualdo, Loreto (Frontiers in Nutrition, 2022)
Obesity is the epidemic of our era and has an incidence supposed to increase more than 30% in 2030. It is commonly defined as a chronic and metabolic disease with an excessive accumulation of body fat in relation to fat free mass, both in terms of quantity and distribution in specific points of the body. The effects of obesity have an important impact in different clinical areas, particularly endocrinology, cardiology, and nephrology. Indeed, the increased obesity rates have been associated with increased risk of cardiovascular disease, cancer, type 2 diabetes, dyslipidemia, hypertension, renal diseases and neurocognitive impairment. Obesity-related chronic kidney disease (CKD) has been ascribed to intra-renal fat accumulation along proximal tubule, glomeruli, renal sinus and around kidney capsule, and to hemodynamic changes with hyperfiltration, albuminuria and impaired glomerular filtration rate. In addition, hypertension, dyslipidemia, and diabetes, which arise as a consequence of overweight, contribute to amplify renal dysfunction both in native and transplanted kidney. Overall, several mechanisms are closely related to the onset and the progression of CKD in the general population, including changes in renal hemodynamics, neurohumoral pathways, renal adiposity, local and systemic inflammation, dysbiosis of microbiota, insulin resistance and fibrotic process. Unfortunately, there are no clinical practice guidelines for managing obesity-related CKD patients. Therefore, the dietary management is based on the guidelines of the clinical practice for nutritional care of adults with CKD, developed and published by the National Kidney Foundation, Kidney Disease Outcome Quality Initiative (K/DOQI) and common recommendations for the healthy population. Optimal nutritional management of these patients should follow the guidelines of the Mediterranean diet (MD), known to be associated with reduced cardiovascular disease incidence and beneficial effects on chronic diseases such as diabetes, obesity or cognitive health. Mediterranean-style diets are often unsuccessful in promoting efficient weight loss, especially in those patients showing altered glucose metabolism. To this purpose, in this review we also discuss the use of non-classical weight loss approaches in CKD, including intermittent fasting (IF) and ketogenic diet (KD) to contrast obesity-related CKD onset and progression.